Enric Miralles: Spacing the Dwelling. Multiplication, Fragmentation and Diversification of a Measured Space Based on the Site - Rocchi, Elena (Universidad de Lima. Carrera de Arquitectura, 2017)
The essay proposed means to me the opportunity to think about the dwelling space understood as the housing design technique through the representation of physical and existential elements. I have done it by connecting myreflections on the site and the results of my professional experience in designing elaborated housings with Enric Miralles (6 housings in Amsterdam 1996/1998), and the results from another experience which took place during my academic experience celebrated both at the ESARQ-UIC, Barcelona, NIROX Foundation of Johannesburg and at ASU Design School, Tempe (desde 2008 hasta la fecha). These reflections make evident the importance in Miralles’ architecture of dialectic in between design and drawing — between internal-external architecture (physical) and the interior and exterior of each of us (existential).